STORY-PARABLE BY IVAN FRANKO «WALK OF LIFE IN THE LEG»: POETICS AND SEMANTICS - Legky, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The problem of poetic and semantic in Franko’s story-parable “Blackthorn in the leg”, in particular the genre nature of the work, it’s imagery, the psychologism of image, style (the features of impressionism, symbolism and gothic are detected) is reviewed in the article; the main author’s ideas, especially the idea of theodicy, are found out.